2013
DOI: 10.7314/apjcp.2013.14.3.1635
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Proteins of Helicobacter pylori of Potential Diagnostic Value

Abstract: Helicobacter pylori antigen was prepared from an isolate from a patient with a duodenal ulcer. Serum samples were obtained from culture-positive H. pylori infected patients with duodenal ulcers, gastric ulcers and gastritis (n=30). As controls, three kinds of sera without detectable H. pylori IgG antibodies were used: 30 from healthy individuals without history of gastric disorders, 30 from patients who were seen in the endoscopy clinic but were H. pylori culture negative and 30 from people with other diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 69 publications
0
16
1
Order By: Relevance
“…Moreover, aberrant diagnosis and treatment may lead to drug misuse subject to unpredictable side effects. There are many immunoassays that have been developed for the diagnosis of anti-H. pylori class serum antibodies (IgG/IgM/IgA) (Khalilpour et al 2014a;Khalilpour et al 2013). The diagnosis of H. pylori infection markers via serology is the easiest noninvasive method for diagnosing an infection as it requires only a few drops of blood from the finger and the results are available in less than 5 min.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, aberrant diagnosis and treatment may lead to drug misuse subject to unpredictable side effects. There are many immunoassays that have been developed for the diagnosis of anti-H. pylori class serum antibodies (IgG/IgM/IgA) (Khalilpour et al 2014a;Khalilpour et al 2013). The diagnosis of H. pylori infection markers via serology is the easiest noninvasive method for diagnosing an infection as it requires only a few drops of blood from the finger and the results are available in less than 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…2). Out of the four H. pylori infection markers identified by Khalilpour et al, UreG, CagI, and pyroline-S-carboxylate dehydrogenase were reported for the first time (Khalilpour et al 2014a;Khalilpour et al 2012;Khalilpour et al 2013;Noordin et al 2013).…”
Section: Virulence Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…SDS-PAGE and Western blotting were performed as described previously. 24 Each AgB batch was mixed 1:4 with 5 + sample buffer (0.3125 M TrisHCl [pH 6.8], 10% SDS, 50% glycerol, 0.005% bromophenol blue, and 25% 2-mercaptoethanol), and 20 μg sample/well was electrophoresed in a 12% (vol/vol) SDS-PAGE gel in fresh running buffer (0.3% Tris, 1.44% glycine, and 0.1% SDS [pH 8.3]) at a constant current of 100 V for 110 minutes. Proteins were transferred from the gel onto a nitrocellulose membrane using the Trans-Blot SD Semi-Dry Electrophoretic Transfer Cell (Bio Rad) at a constant current of 12 A for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%